Proposed Strategy Formulation for an Organic Rice Company - Ningrum, Astrid Hapsari; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2015)
Abstract.Rice is the staple food of Indonesia that the number of its demand increases annually in line with the increase of population. In 2010, M Group formed M Pure Farming (MPF) as Department who responsible for developing rice business as a follow-up of the advantages in built good relationships with farmers before. Not to selling some conventional rice products, MPF intend to sell rice that takes account into health aspects in form of organic, which means do not use pesticides or chemicals at all, as well as help preserve the environment today which has become a public concern. With B2B (Business-to-Business) business model, MPF make purchases of rice to farmers and then sell them under the label of MPF rice.Several issues raised by MPF currently are their market, their supply, and their skills of human resources.MPF market is divided by M Group internal market (1) and external market outside the M Group (2) with total sales of approximately 50 tons per year. Unfortunately, after nearly four years of running, this amount is still only capable of holding about 10% of the internal market potential M Group. So it does with the external market, the intended target remains unclear and sales are in smaller quantities than the internal market for sure. Based on the analysis, MPF needs to improve their strategy to run the business. They need a clear strategy to maximize its internal capabilities and take advantage of opportunities that exist to be able to control intended markets.A good strategy requires analysis of both internal and external environment with several tools such as PESTEL, Porter's 5 Forces, Value Chain, and Resource-Based View (RBV). The results of the environmental analysis are then summarized in a SWOT analysis that serves as a tool in the preparation of the new strategy. The proposed implementation based on previous analysis begin with improvements in their internal management, start in human resource management and corporate culture as basic improvement to improve their employees to be able to improve business process and produce some qualified and valuable products, hence the customers will perceived MPF products as reliable products and maintain the purchasing continuously. Afterwards, in 2020 MPF expected to be able to increase sales of at least up to 500 tons / year and can control the internal market M Group as well as penetrate the right external market in form of Business-to-Business model.The proposed strategy is reflected in the implementation of short and long-term programs, each with its resource requirements and schedules required. The proposed strategy are divided in to three levels, namely Corporate Strategy (1) which suggest MPF to implement growth strategies, Business Strategy (2) that supports corporate strategy which suggest MPF to perform differentiation in its products and services, and Functional Strategy (3) which outlines how each division can implement the established strategy.Key Words : Organic Rice, StrategyÂ